RP-HPLC determination of the lipophilicity of bispyridinium reactivators of acetylcholinesterase bearing a but-2-ene connecting linker - Musilek, Kamil; Jampilek, Josef; Dohnal, Jiri; Jun, Daniel; Gunn-Moore, Frank; Dolezal, Martin; Kuca, Kamil (Analytical and bioanalytical chemistry, 2008)
New acetylcholinesterase reactivators with either a (E) or (Z)-but-2-ene connecting linker were recently prepared. The purity of the compounds was checked by HPLC and was found to be sufficient for in-vitro screening. All the discussed bispyridinium reactivators were analyzed by reversed-phase high performance liquid chromatography (RP-HPLC) to measure lipophilicity. The procedure was performed under isocratic conditions with methanol as organic modifier in the mobile phase using an end-capped non-polar C(18) stationary phase RP column. Relationships between the lipophilicity (logarithm of the RP-HPLC capacity factor, log k) and chemical structures of the studied compounds are discussed. Lipophilicity was different for the (E) and (Z) compounds and varied among the compounds in each of these groups. The lipophilicity differences also indicated an apparent influence of intramolecular interactions. Lipophilicity calculations (log P/Clog P) by means of commonly used software were not successful due to the presence of quaternary nitrogen atoms in the molecules of the reactivators.
Keywords: Pyridinium Compounds; lipidy; vysokoúčinná kapalinová chromatografie; Molecular Structure; Stereoisomerism; pyridinové sloučeniny; reagencia zkříženě vázaná; molekulární struktura; Chromatography, High Pressure Liquid; Drug Contamination; Vinyl Compounds; Cross-Linking Reagents; kontaminace léku; reaktivátory cholinesterasy; Lipids; stereoizomerie; vinylové sloučeniny; Cholinesterase Reactivators